Preparação e caracterização de vidrados obtidos a partir do pó de aciaria elétrica para aplicação em revestimentos cerâmicos - Silva, Vanessa Santana (2020)
Electric-arc furnace dust (EAFD) is a by-product of the steelmaking industry. According to ABNT NBR 10004/2004 standard, the EAFD is considered a class I toxic solid waste. However, EAFD has great potential to be reused as a raw material in glazing preparation, since this material has a small particle size and high iron oxide content. Thus, the aim of this work is to evaluate the viability of EAFD as a pigment to produce glazes and to be applied on ceramic tiles. The EAFD was characterized as to its physical, chemical, structural, thermal and magnetic properties. Next, the EAFD was treated by three magnetic separation methods. The magnetic fractions were used in the glaze preparation and the color analysis was performed. Additionally, non-magnetic fractions generated from the treatment were incorporated into the ceramic substrate, and their technological and structural properties were determined. The results of EAFD characterization showed most of this dust are composed of iron oxide and zinc oxide and the phases related to these compounds are magnetite and zincite, respectively. Due to the presence of magnetite, this dust has magnetic properties and has saturation magnetization of 35.52 emu.g-1 . Finally, thermal analyses have shown that this dust has thermal stability up to 1200 °C. In turn, the results of chemical, structural analysis and magnetic analyses showed that the most effective methods of separation were panning with dry magnetic separation (ETP), wet magnetic separator (ETSW) and wet magnetic separation with magnet 3 (ETM3). Finally, the glazes obtained with the magnetic fractions showed shades of yellow. Additionally, the technological tests and the structural characterization performed on the ceramic tiles showed that the addition of 2.5% non-magnetic fractions to the clay-based formulations did not influence the technological properties of the ceramic tiles and the crystalline phases present after firing.